ANALISIS KESESUAIAN PENERAPAN PRODUK PEMBIAYAAN MUSYARAKAH BERDASARKAN PSAK 106 PADA PT. BPRS HIKMAH WAKILAH - Novisra, Lisandi; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to determine and analyze the application of musharakah financing products and the suitability of the accounting treatment of musharakah financing products applied in PT. BPRS Hikmah Wakilah according to PSAK 106. The research method used is descriptive qualitative. Sources of data in this study are primary data obtained directly from the results of interviews with respondents. The results of the study show that in terms of recognition and measurement of PT. BPRS Hikmah Wakilah is not fully comply in according to PSAK 106, and in terms of the presentation of PT. BPRS Hikmah Wakilah has fully complied with PSAK 106, while in terms of disclosure of PT. BPRS Hikmah Wakilah has not presented CALK and all terms relating to the musharakah transaction. Hence, its application does not comply with PSAK 106.